2013
DOI: 10.1111/jan.12070
|View full text |Cite
|
Sign up to set email alerts
|

A suicidal recovery theory to guide individuals on their healing and recovering process following a suicide attempt

Abstract: Nurses could use this theory as a theoretical framework to guide people who are recovering from a suicide attempt by affording them the opportunity to grow and heal, and facilitating the re-building a positive sense of self, acknowledging the uncertainties of life, and inspiring hope.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 11 publications
3
35
0
2
Order By: Relevance
“…Previous research also indicates that moderate and regular exercise can improve cancer patients' body functional performance and mood, reduce treatment-related adverse effects, and improve quality of life. 36,44,45 Participants indicated that help from support systems also helped them respond to the illness and its related physical and emotional stress from the chemotherapy. The main support system was family including parents, spouse, siblings, and children (n = 13) and clinicians (n = 13).…”
Section: N Discussionmentioning
confidence: 97%
“…Previous research also indicates that moderate and regular exercise can improve cancer patients' body functional performance and mood, reduce treatment-related adverse effects, and improve quality of life. 36,44,45 Participants indicated that help from support systems also helped them respond to the illness and its related physical and emotional stress from the chemotherapy. The main support system was family including parents, spouse, siblings, and children (n = 13) and clinicians (n = 13).…”
Section: N Discussionmentioning
confidence: 97%
“…However, few studies have investigated the suicidal process by conducting qualitative interviews with survivors of suicide attempts (Lakeman & Fitzgerald 2008;Rivlin et al 2013). Still, fewer studies have been conducted with older people in this way (Crocker et al 2006;Im & Kim 2011;Sun & Long 2013). Crocker et al (2006) explored older people's understandings of the pathway to and from a suicide attempt, while Im and Kim (2011) investigated the meanings attributed by older people to experiences prior to their suicide attempt.…”
Section: Towards a Prospective Lens To Improve Understanding Of Protementioning
confidence: 99%
“…These incidents may induce feelings of regret and guilt, and they can even affect the development of an entire community (Holm & Severinsson, ). Previous studies have found that common reactions to suicidal events include sadness, loneliness, depression, confusion, sadness and feelings of guilt (Holm & Severinsson, ; Sun & Long, ). Because of widespread media coverage, if television channels or other media outlets provide a detailed report of the suicide, suicidal emulation can happen (Center for Disease Control and Prevention, ).…”
Section: Introductionmentioning
confidence: 99%
“…Most suicide research has focused on the rates, assessment, prevention and treatment of suicide and on the bereavement care of survivors (World Health Organization, ). Recently, suicide research has started exploring suicidal recovery (Bergmans et al, ; Chi et al, ; Holm & Severinsson, ; Ke, ; Sun & Long, ). However, there is a lack of research on the factors predicting suicidal recovery.…”
Section: Introductionmentioning
confidence: 99%